The other Wes Moore : the story of one name and two fates - Moore, Wes, 1978- (Spiegel & Grau, 2010)
Two kids with the same name were born blocks apart in the same decaying city within a few years of each other. One grew up to be a Rhodes Scholar, army officer, White House Fellow, and business leader. The other is serving a life sentence in prison. Here is the story of two boys and the journey of a generation.